“All-In-One” Genetic Tool Assessing Endometrial Receptivity for Personalized Screening of Female Sex Steroid Hormones - Deryabin, Pavel; Domnina, Alisa; Gorelova, Inga; Rulev, Maxim; Petrosyan, Mariya; Nikolsky, Nikolay; Borodkina, Aleksandra (Frontiers in Cell and Developmental Biology, 2021)
Endometrium is the uterine lining that undergoes hundreds of cycles of proliferation, differentiation, and desquamation throughout a woman's reproductive life. Recently, much attention is paid to the appropriate endometrial functioning, as decreased endometrial receptivity is stated to be one of the concerns heavily influencing successes of embryo implantation rates and the efficacy of in vitro fertilization (IVF) treatment. In order to acquire and maintain the desired endometrial receptivity during IVF cycles, luteal phase support by various progestagens or other hormonal combinations is generally recommended. However, today, the selection of the specific hormonal therapy during IVF seems to be empirical, mainly due to a lack of appropriate tools for personalized approach. Here, we designed the genetic tool for patient-specific optimization of hormonal supplementation schemes required for the maintenance of endometrial receptivity during luteal phase. We optimized and characterized in vitro endometrial stromal cell (ESC) decidualization model as the adequate physiological reflection of endometrial sensitivity to steroid hormones. Based on the whole transcriptome RNA sequencing and the corresponding bioinformatics, we proposed that activation of the decidual prolactin (PRL) promoter containing ancient transposons MER20 and MER39 may reflect functioning of the core decidual regulatory network. Furthermore, we cloned the sequence of decidual PRL promoter containing MER20 and part of MER39 into the expression vector to estimate the effectiveness of ESC decidual response and verified sensitivity of the designed system. We additionally confirmed specificity of the generated tool using human diploid fibroblasts and adipose-derived human mesenchymal stem cells. Finally, we demonstrated the possibility to apply our tool for personalized hormone screening by comparing the effects of natural progesterone and three synthetic analogs (medroxyprogesterone 17-acetate, 17α-hydroxyprogesterone caproate, dydrogesterone) on decidualization of six ESC lines obtained from patients planning to undergo the IVF procedure. To sum up, we developed the “all-in-one” genetic tool based on the MER20/MER39 expression cassette that provides the ability to predict the most appropriate hormonal cocktail for endometrial receptivity maintenance specifically and safely for the patient, and thus to define the personal treatment strategy prior to the IVF procedure.